2021
DOI: 10.1145/3479553
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence Leads to the Formation of Diverse Local Trends

Abstract: How does the visual design of digital platforms impact user behavior and the resulting environment? A body of work suggests that introducing social signals to content can increase both the inequality and unpredictability of its success, but has only been shown in the context of music listening. To further examine the effect of social influence on media popularity, we extend this research to the context of algorithmically-generated images by re-adapting Salganik et al's Music Lab experiment. On a digital platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Secretan et al (2011). Feed the Ganimals allowed users to explore and curate AI-generated hybrid animals, and found that social cues led to the formation of diverse local trends (Epstein et al, 2020a(Epstein et al, , 2021.…”
Section: Related Workmentioning
confidence: 99%
“…Secretan et al (2011). Feed the Ganimals allowed users to explore and curate AI-generated hybrid animals, and found that social cues led to the formation of diverse local trends (Epstein et al, 2020a(Epstein et al, , 2021.…”
Section: Related Workmentioning
confidence: 99%